(untitled) (Journal of Preventive and Social Medicine, 2022)
Background: Perceived Mental Stress (PMS) is an inevitable component of life. During COVID-19 pandemic, it’s ongoing and unpredictable situation has been increasing PMS among women. This present study was designed to compare the PMS level between employed and unemployed women. Methods: This comparative cross sectional study was conducted among purposively selected 240 women; of them 120 employed women are bankers, teachers and other sectors employees and 120 unemployed women are housewives. Data were collected from these participants by using a pre tested semi structured questionnaire and PMS was assessed by using Perceived Stress Scale (PSS) Bangla version. The collected data were analyzed by using SPSS software (Version 20) and p < 0.05 considered as statistical significant. Results: In this comparative study, the mean (±SD) score of PMS between employed and unemployed women found 20.0 (±5.48) and 20.5(±5.16) respectively, which was not statistically significant (p>0.05). The majority (81.7%) of employed women and (80.8%) of unemployed women suffered from moderate stress which was not statistically significant (p>0.05). There exist significant association between PMS and socio-demographic characteristics i.e. educational qualification (p=0.04), complete recovery from COVID-19 (p=0.02) in employed women; where as in unemployed women monthly family income (p=0.03), knowledge on specific treatment of COVID-19 (p=0.02) were significantly associated with PMS. Conclusion: The study revealed no significant difference in PMS between employed and unemployed women and but some associated factors lead them to stressful situation. So, equal emphasis should be given on both employed and unemployed women to prevent perceived mental stress. JOPSOM 2021; 40(2): 52-57